2015
DOI: 10.1186/s12879-015-1280-6
|View full text |Cite
|
Sign up to set email alerts
|

What is needed to guide testing for anorectal and pharyngeal Chlamydia trachomatis and Neisseria gonorrhoeae in women and men? Evidence and opinion

Abstract: BackgroundAnorectal and pharyngeal infections with Chlamydia trachomatis (CT) and Neisseria gonorrheae (NG) are commonly observed in men who have sex with men (MSM). There is increasing evidence that such infections at extra-genital sites are also common in women. In both sexes, these infections are largely overlooked as they are not routinely tested for in regular care. Testing based on sexual behavior or symptoms would only detect half of these extra-genital infections. This paper elucidates the differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 85 publications
1
85
1
2
Order By: Relevance
“…14 Self-collection of rectal and vaginal samples is accurate, may be preferable to provider collection, and may be one way to further increase screening. 2729 …”
Section: Discussionmentioning
confidence: 99%
“…14 Self-collection of rectal and vaginal samples is accurate, may be preferable to provider collection, and may be one way to further increase screening. 2729 …”
Section: Discussionmentioning
confidence: 99%
“…As well as urogenital infections, chlamydia can also cause anorectal infections, with anorectal prevalences found between 5.6% and 17.5%. 2 Women with anorectal chlamydia infection often have a concurrent urogenital chlamydia infection (71-95%) and vice versa (33-83% with a urogenital infection have a concurrent anorectal infection). 2 Anorectal testing for chlamydia is often advised on indication in women with anal symptoms or recent anal sex.…”
Section: Introductionmentioning
confidence: 99%
“…2 Women with anorectal chlamydia infection often have a concurrent urogenital chlamydia infection (71-95%) and vice versa (33-83% with a urogenital infection have a concurrent anorectal infection). 2 Anorectal testing for chlamydia is often advised on indication in women with anal symptoms or recent anal sex. [3][4][5] Studies on routine universal anorectal testing consistently found similar anorectal chlamydia prevalence in women with or without anal symptoms or history of anal sex.…”
Section: Introductionmentioning
confidence: 99%
“…3 Importantly, up to 20% of cases of the HELLP syndrome develop in women without previous onset of hypertension. 4 The area under the curve in the receiver-operating-characteristic analysis for prediction of preeclampsia or the HELLP syndrome within 1 week Since publication of their article, the authors report no further potential conflict of interest. …”
Section: Doi: 101056/nejmc1602338mentioning
confidence: 99%
“…3 Such infections are also common in women, although with additional testing for rectal and oropharyngeal infection, the increment is less. 4 Many anecdotal reports have indicated that azithromycin is less effective than doxycycline for the treatment of rectal, oropharyngeal, or genital infection. For example, in a retrospective cohort study, 23 of 136 men (17%) tested positive for chlamydia infection 14 to 60 days after treatment with azithromycin, and 0 of 36 men tested positive 14 to 60 days after treatment with doxycycline.…”
Section: Azithromycin Versus Doxycycline For Chlamydiamentioning
confidence: 99%